Manual on Fiscal Transparency. (Manuals and Guides, 2002)
This Manual provides guidance on the implementation of the Code of Good Practices on Fiscal Transparency by setting out its principles and practices in detail, and establishing priorities for improving fiscal transparency. Serving as a reference for economists and financial analysts on the various aspects of fiscal transparency, the Manual includes a section on open budget preparation, execution, and reporting, and presents the OECD's best practices for achieving budget transparency.